Effect of Giving Fermented Gold Snail (Pomacea canalicuta L) Flour Using Eco Enzymes on Digestibility of Dry Matter and Organic Matter in Quail (Jurnal Peternakan Integratif, 2022)
Quail is a source of protein and highly nutritious animal. Feed is the basic need of every animal.The cost of feed is very high, reaching 70% of the total cost of producing quail.Gold snail (Pomacea canalicuta L) has the potential to be used as feed raw material because of its abundant availability.Eco-enzyme is a fermented that can be used in gold snail fermentation. So it is necessary to do the digestibility of dry matter and organic matter in quail fed with golden snail flour fermented using eco-enzymes.The research design used was a completely randomized design (CRD) with 4 treatments and 5 replications. The parameters studied were dry matter consumption, consumption of organic ingredients, dry matter digestibility (Kcbk) and organic matter digestibility (Kcbo). Based on the results of the study, it was known that feeding using gold snail flour fermented using eco-enzymes in the ration as much as 12% got the best results